Regularity of the Solution to the Dirichlet Problem in Morrey Spaces (Journal of Partial Differential Equations, 2002)
" The aim of this paper is to study Morrey regularity of the solution to the Dirichlet problem for second order elliptic equation of the form Lu = -(a_{ij}u_x_i + b_j_u)_x_j + du = e + (f_j)x_j in a bounded open subset of Rn(n \u2265 3), where b_j , d, e, f_j are assumed to be in some Morrey spaces."